Faktor-Faktor Yang Mempengaruhi Secara Langsung Maupun Tidak Langsung Ketimpangan Distribusi Pendapatan - Pauzi, Ahmad; Budiana, Dewa Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 6, Juni 2016 (pp. 652-728), 2016)
Inequality of income distribution in the province of Bali is one of the serious problems, it is because of growth in each district / city different. The purpose of this study is to see whether economic growth is a variable mediating the indirect effect of exports and foreign investment to the unequal distribution of income. This study uses data from the data panel comprising eight counties and one city in the period 2007-2013. The analysis technique used is path analysis. Based on the analysis found that the export of positive and significant effect on economic growth, while foreign investment is not significant to the economic growth. Economic growth is positive and significant effect on the unequal distribution of income. Meanwhile, the direct effect of exports on income inequality of food distribution having an negative and significant, whereas the effect of direct foreign investment to the unequal distribution of income does not significantly, and economic growth is a variable mediating the indirect effect of exports and foreign investment to the unequal distribution of income
Keywords: Unequal Distribution Of Income, Exports, Foreign Investment, Economic Growth